Is early childhood exposure a key predictor of adulthood problematic gaming? - Shannon A. H. Compton; Paul F. Tremblay; Elizabeth A. Osuch; Derek G. V. Mitchell (PLoS ONE, 2026)
Internet Gaming Disorder (IGD) is a proposed condition wherein a preoccupation with video games causes distress and functional impairment. However, the extent to which IGD resembles substance use disorders is controversial. In substance-related disorders, the timing of first exposure correlates with adult symptom severity; however, it is unclear whether IGD symptoms share a similar pattern. The present study used growth mixture modelling to identify how the onset of frequent gaming during early life relates to problematic gaming in adults. A four-class model that differentially predicted current IGD symptoms was identified. The ‘Consistently High Group’ (high levels of gaming during childhood and adolescence) displayed higher IGD symptoms than the ‘Low Escalating Group” (low gaming during these stages) and ‘Rapidly Escalating Group’ (low gaming during preschool followed by high gaming). However, the ‘Consistently High Group’ did not show greater IGD symptoms than the ‘Moderate Group,’ which was the only other group with substantial preschool gaming. Regression analyses confirmed that gaming during preschool and high school predicted current IGD symptoms, with preschool gaming being the strongest predictor. This study highlights additional parallels between substance-related disorders and IGD, specifically identifying an early age of onset as a predictor of adult symptom severity. These results may inform caregivers and paediatric guidelines concerning when and how video game play is introduced and motivate further research clarifying how problematic gaming may emerge through interactions between developmental exposure, mental health, environmental factors, and individual traits.